The Impact of Combined Pulmonary Fibrosis and Chronic Obstructive Pulmonary Disease on Long-Term Survival after Lung Cancer Surgery - Sekine, Yasuo; Sakairi, Yuichi; Yoshino, Mitsuru; Koh, Eitetsu; Hata, Atsushi; Suzuki, Hidemi; Yoshino, Ichiro (The Thoracic and Cardiovascular Surgeon, 2014)
Purpose The purpose of this study was to determine the impact of pulmonary fibrosis (PF) on postoperative complications and on long-term survival after surgical resection in lung cancer patients with chronic obstructive pulmonary disease (COPD).Patients and Methods A retrospective chart review was conducted of 380 patients with COPD who had undergone pulmonary resection for lung cancer at the University Hospital between 1990 and 2005. The definition of COPD was a preoperative forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) ratio of less than 70%; PF was defined as obvious bilateral fibrous change in the lower lung fields, confirmed by computed tomography.Results PF was present in 41 patients (10.8%) with COPD; the remaining 339 patients (89.2%) did not have PF. The preoperative FVC/FEV1 was significantly lower in the group of patients with PF than in the group without (p < 0.05). Acute lung injury and home oxygen therapy were significantly more common in the PF group; however, the 30-day mortality was similar between the groups. The cumulative survival at 3 and 5 years was 53.6 and 36.9%, respectively, in the PF group and 71.4 and 66.1%, respectively, in the non-PF group (p = 0.0009). Increased age, decreased body mass index, advanced pathologic stage, and the existence of PF were identified as independent risk factors for decreased survival.Conclusion PF is a risk factor for decreased survival after surgical treatment in lung cancer patients with COPD.
Keywords: lung cancer; chronic obstructive pulmonary disease; pulmonary fibrosis; combined pulmonary fibrosis and emphysema